A centralized local energy storage modular multilevel converter - Li, Ning; Xiao, Zihan; Jiang, Panyong; An, Zhuoer; Li, Zhuang; Wang, Yelin (Frontiers in Energy Research, 2022)
The energy storage modular multilevel converter (MMC-ES) has been widely studied for its excellent performance in solving the problems of power difference and voltage fluctuation caused by new energy grid connection. Aiming at the problems that energy storage units of the traditional distributed MMC-ES are scattered, inconvenient to assemble and maintain, complex system control, and the traditional centralized MMC-ES has poor capacity selection flexibility, in this paper, a centralized local energy storage modular multilevel converter (MMC-CLES) between the distributed MMC-ES and the centralized MMC-ES is proposed. On the premise of not affecting the advantages of MMC-ES, by reducing the number of energy storage units, the switching loss is reduced, and the problems of complex SOC (state of charge) balance control strategy, large power conversion system loss and high system cost caused by too many energy storage units are solved. Matlab/simulink simulation shows that compared with traditional distributed MMC-ES, MMC-CLES reduces a total of 52 power devices, and under the condition of three-phase voltage unbalance, the SOC balance control and the fast balance of the three-phase current are realized. The unbalance degree of the three-phase current is 8.16%, and the total harmonic distortion rate of the current is 3.11%.